Alentejo blue fiction - Ali, Monica 1967- (Scribner, 2006)
This is the story of a village in Portugal, told through the lives of men and women whose families have lived there for generations and some who are passing through. For Teresa, a beautiful girl not yet twenty, Mamarrosa is a place from which to escape. For the dysfunctional Potts family, it is a way of running from trouble. Vasco, a café owner who has never recovered from the death of his American wife, clings to a notion that his years away from the village, in the States, make him superior. One English tourist fantasizes about making a new life here; for her compatriots, a young engaged couple, this is where their dreams fall apart. The village awaits the homecoming of its prodigal son, now a symbol of the fast-changing world. When he finally returns, villagers, tourists, and expatriates are brought together, and their jealousies and disappointments inevitably collide.--From publisher description.
Keywords: Alltag, Brauchtum; Portugal -- Social life and customs -- Fiction; Fiktionale Darstellung